Smart metering in Germany and Austria: Results of providing feedback information in a field trial - Joachim Schleich; Marian Klobasa; Marc Brunner; Sebastian Gölz; Konrad Götz (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2011)
In this paper, we present the results from a field study on smart metering in Germany and Austria, focusing on the effects of providing feedback information on average electricity consumption. Econometric analyses are applied using a cross section of observations for more than 2000 households served by nine utilities. More than half of these households received feedback on their electric-ity consumption together with information about electricity saving measures (pi-lot group). The remaining households served as a control group. To evaluate the impact of feedback information, we econometrically estimated household electricity consumption. Explanatory variables include a wide range of socio-economic factors (income, education, age, household size, age composition, etc.) as well as the household appliance stock (large appliances, boiler, com-puters, TV, etc. ...). The results suggest that the feedback provided under the smart metering programme results in electricity savings of around 3.7%.
Keywords: 330; Smart metering; feedback; household electricity consumption; Elektrizitätswirtschaft; Messgerät; Energiesparen; Privater Haushalt; Energiekonsum; Deutschland; Österreich